Penerapan Media Film Kartun pada Mata Pelajaran Bahasa Indonesiadi SD Swasta Patria Al-Ittihadiyah Percut Sei Tuan Deli Serdang - Elza Zairima; Rustam Rustam; Lailatun Nur Kamalia Siregar (LPPM Politeknik Pratama, 2024)
This study aims to determine how the application of cartoon film media in Class V students of Indonesian language subjects at Patria Al Ittihadiyah Private Elementary School Percut Sei Tuan Deli Serdang and the obstacles that occur in the implementation of Indonesian language learning by using cartoon film media in class V students of Patria Al-Ittihadiyah Private Elementary School Percut. This research is a type of qualitative research and uses a descriptive qualitative approach method. Data obtained through several sources, namely observation, interviews, and documentation data supporting visual learning media, the availability of textbooks and the activeness of Al-Ittihadiyah Private Elementary School teachers in participating in trainings related to learning media. The application of cartoon film media in Indonesian language subjects in class V has been running quite well by using a projector as an auxiliary tool. However, there are several obstacles that hinder the learning process using this media, including: first, the lack of technicians who can operate projectors and make powerpoints to become learning media, second, there are still many teachers in this elementary school who do not understand the technology that has developed rapidly in this digital era. Thus, the Principal has an initiative to add an operator who can provide direction to teachers in this elementary school so that they can use learning media for students. Because with this learning media, it is more inviting for students during lesson hours.